Impact of Blockchain Technology Platform in Changing the Financial Sector and Other Industries - Dusko Knezevic (Montenegrin Journal of Economics, 2018)
The aim of the paper is to conduct a research on an impact of blockchain technology platform on the financial sector through cryptocurrency, and an impact on other industries.. The subject of research is not only this technology but also its commercial exploitation. In order to understand the platform, the starting point of this research is an analysis of how the technology functions, after that the advantages for business and economic transaction are identified, and finally the paper deals with an impact of new technology on business, above all on financial operations. The basic hypothesis is that blockchain has achieved a great impact on financial sector, also it has the potential to radically change only the financial sector but also the way we buy and sell, our interaction with the authorities as a way of verifying the ownership from the authorship and the organic food production. Using the available data and synthesis of knowledge from the fields of technology, economics, finance, and politics, 4 scenarios were set up for the future of underlying technology. The scenario approach combined with trend analysis in order to prove the starting hypothesis with high reliability. The research results show that the technology being investigated already has a profound impact on the financial sector, that it is in the initial phase of changing many industries, with the likelihood that they will change them significantly in the next five to ten years. Businesses increasingly discover the power of this technology to exploit the benefits of the Fourth Technological Revolution.